Pengaruh Pendapatan Asli Daerah Dana Bagi Hasil dan Dana Alokasi Khusus Terhadap Belanja Modal Pada Pemerintahan Dapil II Provinsi Aceh - Marzuki Marzuki; Husaini Husaini; Chairil Akhyar; Radiah Alfara (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2021)
This study aimed to determine the effect of Own-source Revenue, Profit Sharing Funds, and Special Allocation Funds on Capital Expenditures in the Government of Electoral District II Aceh. The data used in this study are reports on the realization of the APBD from 2014-2019. The data analysis method used was multiple linear regression using SPSS and three classical assumption tests (normality test, multicollinearity test, and heteroscedasticity test). The results partially showed that Own-source Revenue and revenue sharing funds significantly influenced capital expenditures in the government of electoral districts of Aceh. Meanwhile, the Special Allocation Fund insignificantly influenced capital expenditures in the Aceh district government. Simultaneously, Own-source Revenue, Profit Sharing Funds, and Allocation Funds influenced Capital Expenditures in the two electoral governments of Aceh. Keywords: Own-source Revenue, Profit Sharing Fund, Special Allocation Fund, Capital Expenditure.